Mechanical, electrical and tribological properties of graphite filled polyamide-6 composite materials - ESMER, KADİR (WALTER DE GRUYTER GMBH, 2013)
In this study, the influence of adding graphite filler, on the mechanical, electrical and tribological properties of nylon-6 composites, is studied. Graphite fillers with different percentages, varying between 5 and 15 wt% were added to nylon-6 polymer material. Nylon-6 composite samples were prepared by the injection molding process. Tensile, impact, electrical and tribological tests were carried out and the dielectric permittivity tangent loss factor, tensile strength, modulus of elasticity, elongation at break, impact strength, specific wear rate and coefficient of friction properties were obtained. The results showed that the tensile strength, elongation at break, impact strength, and specific wear rate of nylon-6 composites, decrease with the increase in graphite filler weight ratio, while the modulus of elasticity, hardness, real part of dielectric permittivity, imaginary part of dielectric permittivity and dielectric loss, increase with increase in the filler weight ratio. Furthermore, it is observed that a rise in the relaxation time of ionic polarization is proportional to the increase in the amount of graphite in the medium and the dielectric conductivity and loss decrease proportionally after approximately 10 KHz. Finally, the maximum improvement in properties, in total, is recorded following the addition of 5 to 10 wt% graphite filler.
Keywords: composite; dielectric properties; graphite; mechanical; CARBON FILLERS; BEHAVIOR; CONDUCTIVITY; PERFORMANCE; PERCOLATION; FRICTION; NYLON; FIBER; DRY